Evaluation of the anti-fatigue effects of a traditional herbal drug, Gongjin-dan, under insufficient sleep conditions: study protocol for a randomised controlled trial. Issue 1 (December 2016) - Son, Mi Ju; Im, Hwi-Jin; Kim, Young-Eun; Ku, Boncho; Lee, Jun-Hwan; Son, Chang-Gue
Abstract Background Many herbal medicines are traditionally used as anti-fatigue agents in east Asian countries; however, there is a dearth of clinical evidence supporting the anti-fatigue effects of such medicines and their mechanisms. This study is a feasibility trial to assess the clinical efficacy ofGongjin -dan (GJD) and verify its mechanisms by exploring fatigue outcomes, including endocrine and immunological biomarkers in humans. Methods/Design To investigate the anti-fatigue effects of GJD and the mechanism underlying these effects, a randomised, double-blind, placebo-controlled crossover clinical trial was designed. Participants (24 healthy male volunteers) will be hospitalised for 4 days (3 nights), during which acute fatigue and stress conditions will be induced by sleep deprivation, and GJD or a placebo will be administered (twice daily). The primary outcome will be changes in serum cortisol levels, measured in the morning, as an objective biomarker of sleep deprivation-induced fatigue and stress. The secondary outcomes will include: the Fatigue Severity Scale; the Brief Fatigue Inventory, and the Leeds Sleep Evaluation Questionnaire scores; levels of salivary cortisol, epinephrine, norepinephrine, oxidative stress-related biomarkers, homocysteine, and immunological factors; and heart rate variability. After a washout period of more than 4 weeks, a second treatment phase will commence in which participants who were previously administered the placebo will receive the drug and vice versa, following the same treatment regime as in the first phase. Discussion This study protocol provides a unique opportunity to enhance our understanding of fatigue and the effects of GJD on fatigue in terms of endocrine and immunological mechanisms by validating the study design and determining feasibility. Findings from this trial will help researchers to design a pilot or definitive clinical trial of traditional herbal medicine for chronic fatigue. Trial registration Korean National Clinical Trial Registry CRIS;KCT0001681, registered on 29 October 2015.